Flutter recipes : mobile development solutions for iOS and Android - Cheng, Fu (Apress, 2019)
Take advantage of this comprehensive reference to solving common problems when developing with Flutter. Along with an introduction to the basic concepts of Flutter development, the recipes in this book cover all important aspects of this emerging technology, including development, testing, debugging, performance tuning, app publishing, and continuous integration. Although Flutter presents a rich, cross-platform mobile development framework, helpful documentation is not easily found. Here you?ll review solutions to various scenarios and use creative, tested ways to accomplish everything from simple to complex development tasks. Flutter is developed using Dart and contains a unique technology stack that sets it apart from its competitors. This book takes the mystery out of working with the Dart language and integrating Flutter into your already existing workflows and development projects. With Flutter Recipes, you?ll learn how to build and deploy apps freshly started in Flutter, as well as apps already in progress, while side-stepping any potential roadblocks you may face along the way.